An Update Of The Allen & Coggan Equation To Predict 60-Min Power Output In Cyclists Of Different Performance Levels - Sitko, Sebastian; Cirer-Sastre, Rafel; López-Laval, Isaac (International Journal of Sports Medicine, 2023)
The Allen & Coggan protocol suggests that 95% of the power output during a 20-min time trial is a valid surrogate for 60-min maximal power. The validity of this concept has not been studied previously in cyclists with different performance levels. As a result, we classified 120 cyclists in our study as recreationally trained, trained, well trained or professional, based on their maximal oxygen consumption. Participants performed a functional threshold power testing protocol based on a 20-min time trial and a 60-min time trial, separated by a 72-hour rest. Sixty-minute maximal power was successfully modeled with 20-min maximal power and performance group using 2/3 of the dataset (R2=0.77, 95% CrI [0.74, 0.79]) with different coefficients for each group: Professional: PO60min=PO20min × 0.96; well trained: PO60min=PO20min × 0.95; trained: PO60min=PO20min × 0.92 and recreationally trained: PO60min=PO20min × 0.88. The predictions of the original equation and our model were assessed using the remaining third of the data. The predictive performance of the updated equation was better (original: R2=0.51, mean absolute error=27 W, mean bias=–12 W; updated: R2=0.54, mean absolute error=25 W, mean bias=–7 W).
Keywords: coggan & allen test; cycling; physiology; endurance; power meter